TEACHING ENGLISH TO YOUNG LEARNERS IN THE CONTEXT OF INDONESIAN EDUCATION REFORM - Vincentius Luluk Prijambodo (Magister Scientiae, 2016)
Globalization as a social process is inevitable and thus requires nations to join global community of the world. The liberalized economics, modernized culture, and democratized politics as the effects of globalization demand competition and interdependence among nations. Only will human resources with good quality support a country to enhance its competitive power. To contribute to the development of the human resources, some schools in Indonesia have taken into action the strategic decision, that is teaching English to young learners since their early age. English is chosen as the first foreign language to teach because of its status as a global language. This paper focuses on the discussion of the teaching of English to young learners to support the development of human resources in Indonesia.